JAMU HERBAL SEBAGAI REPRESENTASI ETNOSAINS DALAM MENDUKUNG PEMBELAJARAN KONTEKSTUAL MATA PELAJARAN IPA DI SEKOLAH DASAR - Siti Ni'matul Fitriyah; Supriyono Supriyono; Slamet Arifin (Inteligensi : Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze herbal medicine as a representation of ethnoscience in the context of science learning, examine the relevance of herbal medicine to the principles of contextual education in elementary schools, and explore the potential of herbal medicine in supporting science literacy and preserving local wisdom. This study uses a qualitative approach with an ethnographic design. Data were collected through observation, interviews with herbal medicine sellers and consumers, and a documentary study of elementary school curriculum documents. Data analysis was conducted using the Miles and Huberman model and the Gioia method to identify coding, categorization, and main themes. The results indicate that knowledge of herbal medicine has been passed down from one generation to the next. Additionally, herbal medicine sellers also enhance their knowledge through literature and participate in modern training activities organized by the health office. From the consumers' perspective, herbal medicine remains trusted for its empirical benefits, even though its popularity has declined among the younger generation. Documentation of the Merdeka Curriculum reveals that biodiversity learning in fourth-grade elementary school can be effectively integrated with local potential, such as herbal medicine, thereby supporting more contextual science learning. The study's results conclude that herbal medicine can be effectively utilized as a learning medium that bridges traditional knowledge with modern science, while preserving local wisdom. Further research is recommended to develop ethnoscience-based teaching materials, conduct experimental studies on science literacy, and explore other local wisdom relevant to science learning in elementary schools.